Organic waste-borne ZnS nanoparticles: The forgotten ones. (1st September 2022) - Levard, C.; Le Bars, M.; Formentini, T.; Legros, S.; Doelsch, E.
Highlights: Considerably more ZnS-NPs are released into the environment than most commercial NPs. The fate of incidental ZnS-NPs formed in organic waste has been completely overlooked. ZnS-NPs that form in organic waste are small and exhibit unique structural properties. The reactivity and ecotoxicity of ZnS-NPs may be enhanced due to their small size.